Effects of dexmedetomidine dosage on the short-term cognitive function of elderly patients undergoing cardiac surgery - Salman Ahmed; Erum Shahzadi Malik; Riaz Ahmed Qureshi; Syed Zaidan Shuja; Muhammad Umair Siddiq; Javeria Zaheer (Medical Journal of South Punjab, 2024)
Objective: to explore how different infusion rates of perioperative dexmedetomidine (DEX) impacted short-term cognitive function post-surgery. Methodology: Study was conducted at department of cardiothoracic surgery Memon Medical Institute Hospital Karachi, Pakistan between January 2022 and November 2022. DEX infusion before extubation in post operative time was given until 1 hour and divided into two dufferent doses. Low dose (group L) and high dose (group H). Patients were assignded in these groups by lottery method. Group L was given a low-rate DEX infusion of 0.1–0.5 µg/kg/h and Group H was given a high-rate DEX infusion of 0.5–0.9 µg/kg/h. Results: The mean comparison between postoperative outcomes was shown in table. III. The mean MMSE (T0) and MMSE (T1) of the patients was 29.78±3.96 and 25.82±1.78, respectively, (p<0.001). The mean MMSE (T1) and MMSE (T2) of the patients was 25.82±1.78 and 26.65±1.81, respectively, (p=0.015). The mean MMSE (T2) and MMSE (T3) of the patients was 26.65±1.81 and 28.55±2.62, respectively, (p<0.001). The mean MMSE (T3) and MMSE (T4) of the patients was 28.55±2.62 and 29.33±2.93, respectively, (p=0.109). Conclusion: DEX with infusion of low doses (0.1–0.5 µg/kg/h) is superior to high doses (0.5–0.9 µg/kg/h) in cognitive protection for older patients having age 60 years or above.